Pengaruh Gaya Kepemimpinan Terhadap Kinerja Perangkat Desa pada Desa Congko Kabupaten Soppeng - Andi Dirga Patalo; Isma Isma (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Based on the phenomenon that occurred at the Congko Village office, it appears that the performance of village officials has not been optimal, this can be seen from the fact that there are still village officials who do not comply with the applicable rules and regulations, apart from that there are village officials who are indifferent to the tasks given to them. This caused the community to complain about the services provided by village officials at the Congko Village Office. The formulation of the problem in this research is Does leadership style influence the performance of Village officials in Congko Village, Soppeng Regency, while the aim of this research is to determine the influence of leadership style on the performance of Village officials in Congko Village, Soppeng Regency. This research was carried out at the Congko Village office, which is located in Congko Village, Marioriwawo District, Soppeng Regency. The sample was determined using the Census or Saturated Sampling Technique, that is, the total population can be used as the sample size in this research, so that the sample in this research is all Village Officials Congko numbered 13 people. To determine the influence of leadership style on the performance of village officials, simple linear regression analysis was used. From the results of a simple regression analysis, it can be concluded that: Leadership style has an influence on the performance of village officials at the Congko Village Office, Marioriwawo District, Soppeng Regency. The suggestions given by researchers to the Congko Village Government are to maintain and improve the leadership style currently applied so that war performance in Congko Village can improve.